2021
DOI: 10.1097/pts.0000000000000797
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Patients in the Era of Coronavirus: What to Fear Most?

Abstract: Background The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) pandemic led to a worldwide medical crisis, affecting mostly immunocompromised patients, such as cancer patients. Various cancer societies have issued recommendations regarding patients care, but few studies addressed the perception of cancer patients regarding this pandemic. Objective The aim of the study was to assess the perception of cancer patients regarding their health ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 10 publications
0
12
0
Order By: Relevance
“…This phenomenon was also found to be more pronounced among patients with long‐term diagnoses. Other studies have found that a majority of participants feared the pandemic more than they did cancer itself 12 . Zuliani et al 13 found acceptance among patients for most prevention measures; the exception was telephone appointments, which substantial numbers of patients regarded as inadequate, although a survey of patients at the same cancer center being studied in this article found high levels of satisfaction with virtual care 14 .…”
Section: Introductionmentioning
confidence: 67%
See 1 more Smart Citation
“…This phenomenon was also found to be more pronounced among patients with long‐term diagnoses. Other studies have found that a majority of participants feared the pandemic more than they did cancer itself 12 . Zuliani et al 13 found acceptance among patients for most prevention measures; the exception was telephone appointments, which substantial numbers of patients regarded as inadequate, although a survey of patients at the same cancer center being studied in this article found high levels of satisfaction with virtual care 14 .…”
Section: Introductionmentioning
confidence: 67%
“…Other studies have found that a majority of participants feared the pandemic more than they did cancer itself. 12 Zuliani et al 13 found acceptance among patients for most prevention measures; the exception was telephone appointments, which substantial numbers of patients regarded as inadequate, although a survey of patients at the same cancer center being studied in this article found high levels of satisfaction with virtual care. 14 Ciążyńska et al, 15 in a study of 260 patients with cancer in Poland in March 2020, found significantly lower self‐reported quality of life among patients during the pandemic in comparison with the general population.…”
Section: Introductionmentioning
confidence: 74%
“…The studies mainly described the participants’ personal fears and health risk of the virus [ 23 ; 35 ; 41 ; 45 ; 51 ; 57 ; 60 ; 62 ; 67 ; [69] , [70] ] or of the impact it will have on society's resources [ 19 ; [71] , [72] ]. In both cases this is further impacted by the perceived behavior of individuals to either adapt or not to the restrictions imposed on them, but also in the way healthcare services behave in response to the pandemic [ 19 ; 24 ; 45 ; 67 ].…”
Section: Resultsmentioning
confidence: 99%
“…Fear was also expressed as a response to the perceived ability of participants with cancer to respond physically or otherwise to a COVID-19 infection [ 26 ; 28 ; 51 ; 57 ; 71 ], to feel able to continue [ 69 ; 72 ] or curtail their treatment in some way [ 23 ; 45 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation